ADHERENT-INVASIVEE. COLI PROMOTE ER STRESS TO SUPPORT IL23R-DRIVEN AGR2-DEPENDENT ILEOCOLITIS. (22nd January 2022) - Viladomiu, Monica; Khounlotham, Manirath; Dogan, Belgin; Lima, Svetlana; Elsaadi, Ahmed; Herzog, Jeremy; Schoenborn, Alexi; Ellermann, Melissa; Liu, Bo; Zhang, Shiying; Gulati, Ajay; Sartor, R Balfour; et al.
Abstract: Anterior gradient 2 (AGR2) is an epithelial protein disulfide isomerase critical for mucus production and endoplasmic reticulum (ER) homeostasis. Loss-of-function genetic variants in AGR2 are associated with Crohn's disease (CD), and AGR2-deficient mice develop spontaneous ileocolitis, but the specificity of its impact on the host-microbe interaction driving disease is not well understood. Our new data reveals that AGR2 deficiency results in intestinal dysbiosis characterized by the expansion of adherent-invasive E. coli (AIEC). By re-deriving mice germ-free, we show that spontaneous ileocolitis is microbe-dependent and that AIEC isolates, but not other mucosa-associated microbes such as SFB, are sufficient to drive inflammatory disease in the absence of AGR2. AIEC induction of ER stress in AGR2-deficient mice enables further expansion of mucosal Enterobacteriaceae and is required for IL-23R-dependent Th17 cell ileocolitis. These findings reveal a central role for epithelial cell AGR2 in restraining ER stress induced by AIEC to prevent dysbiosis and inflammation in CD.